The 15-minute city: assumptions, opportunities and limitations - Szymańska, Daniela; Szafrańska, Ewa; Korolko, Michał (Bulletin of Geography. Socio-economic Series, 2024)
The concept of the 15-minute city (FMC), though created relatively recently, has quickly become one of the most popular concepts in urban planning. The paper discusses the FMC concept, presenting its evolution from an idea in the public debate to a research concept. The FMC is also presented in relation to other urban planning concepts. The article discusses the assumptions, opportunities and limitations of the FMC. Despite the growing popularity of the concept, it should be remembered that cities are spatial and functional structures that are shaped over a long period of time and show surprising durability (it often being difficult to change or rebuild existing structures); the implementation of this concept is often associated with numerous varied challenges, which are highlighted in this article. Although the assumptions of the concept are very good, it still remains more in the sphere of a concept than of widespread concrete implementation in planning practice